The Impact of Demographic Factors and News Exposure of Child Sexual Abuse in the Mass Media toward Communication Quality of Parents in Providing Sex Education for Children - Nidya Aldila; N S Ulfa; Sri Widowati Herieningsih; Tandiyo Pradekso (Interaksi Online, 2015)
Many cases of child sexual abuse become media spotlight, such as print media, TV, and online. However, not all the audience watch the news. They are motivated by differences in demographic factors, such as gender, age, education level, and income level. The cases spread in the mass media should be concern of many parents to pay more attention to the patterns of communication as a way of parents to control the safety of their children. Sex education is considered to be an appropriate way to provide sexual knownledge to children who are vulnerable from the damage of sexual crimes. However, not all parents are willing to deliver sex education to their children.This study employed the theory of social categories explain the difference between social categories can affect the audience's response when receiving message from mass media (Rakhmat, 2011) and media functionalist theory that explain how media exposure can affect their communication activities that occur between the audience (Mc Quail, 1972). The population of this study were the parents of SD Negeri Padangsari 02 Semarang, who have child 10-12 years old. Sampling was done by simple random technique with a number of 63 respondents.The first hypothesis test indicate that the demographic factors of the three variables, those are gender, age, and educational level when calculated simultaneously using regression analysis techniques, do not affect the news exposure of child sexual abuse in the mass media. While the variable of income level has an impact to the news exposure of child sexual abuse in mass media with significance value of 0,011. The second hypothesis test prove that the news exposure of child sexual abuse in the mass media affects the communication quality of parents in providing sex education with a significance value of 0,001.Advice can be given from this study is that parents should pay more attention to their way to communicate with children, especially regarding sex education. Sex education can be good when it is given according to the child's age and their understanding level considering the number of cases of sexual abuse is increase as in the media.